Radioactivity levels in the marine environment along the Exclusive Economic Zone (EEZ) of Qatar. Issue 1 (15th January 2015) - Al-Qaradawi, Ilham; Abdel-Moati, Mohamed; Al-Yafei, Mohsin Al-Ansi; Al-Ansari, Ebrahim; Al-Maslamani, Ibrahim; Holm, Elis; Al-Shaikh, Ismail; Mauring, Alexander; Pinto, Primal V.; Abdulmalik, Dana; Amir, Amina; Miller, Mark; et al.
Highlights: A first time study of the marine radioactivity in Qatar measured at 15 sites. Samples of seawater, sediments and biota from 2011 to 2012 assessed for gamma radiation. Measured radioactivity levels were low in comparison with similar studies. Low concentration factors, following IAEA standards, indicate safe seafood in Qatar. No significant risk to human health from the marine radioactivity levels in Qatar. Abstract: A study on 137 Cs, 40 K, 226 Ra, 228 Ra, and 238 U was carried out along the EEZ of Qatar. Results serve as the first ever baseline data. The level of 137 Cs (mean value 1.6 ± 0.4 Bq m −3 ) in water filters was found to be in the same order of magnitude as reported by others in worldwide marine radioactivity studies. Results are also in agreement with values reported from other Gulf regions. The computed values of sediment–water distribution coefficients Kd, are lower than the values given by IAEA. Measurements were carried out for bottom sediments, biota samples like fish, oyster, sponge, seashell, mangrove, crab, shrimp, starfish, dugong and algae. The 'concentration factors' reported for biota samples are below the levels published by IAEA and cause no significant impact on human health for seafood consumers in Qatar.